2015
DOI: 10.1007/s00210-015-1085-6
|View full text |Cite
|
Sign up to set email alerts
|

Potencies and unblocking kinetic properties of antagonists at recombinant human NMDA receptors in a Xenopus oocytes model

Abstract: N-methyl-D-aspartate (NMDA) receptor channels are implicated in a wide range of physiological and pathophysiological processes, and a large number of pharmacological agents have been introduced that target the receptor via diverse mechanisms of action. Amongst others, subunit selectivity (in particular for the NR2B receptor subunit) and rapid unblocking kinetics have been put forward as favourable pharmacological properties of NMDA receptor-targeting drugs. Here, we describe a pharmacological characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Parsons et al reported that memantine, amantadine, and dextromethorphan, which have low affinities for NMDA receptors, exhibit obviously faster open-channel blocking/unblocking kinetics than NMDA receptor antagonists associated with severe psychotropic effects, such as PCP or (+)MK-801, which have high affinities for NMDA receptors, and unblocking kinetics are directly related to affinity, namely, lower affinity NMDA receptor antagonists have faster unblocking kinetics [ 50 , 51 ]. Heusler et al also reported that memantine has faster unblocking kinetics than PCP and ketamine, similar to duloxetine, which is also a low-affinity antagonist of NMDA receptors, on recombinant human NMDA receptors [ 52 ] (it is described in more detail in the later Section 4.2 Mode of Fast Off-Rate and Section 4.3 Voltage Dependency).…”
Section: Why Is Memantine Free Of the Severe Side Effects Of Nmda mentioning
confidence: 99%
See 1 more Smart Citation
“…Parsons et al reported that memantine, amantadine, and dextromethorphan, which have low affinities for NMDA receptors, exhibit obviously faster open-channel blocking/unblocking kinetics than NMDA receptor antagonists associated with severe psychotropic effects, such as PCP or (+)MK-801, which have high affinities for NMDA receptors, and unblocking kinetics are directly related to affinity, namely, lower affinity NMDA receptor antagonists have faster unblocking kinetics [ 50 , 51 ]. Heusler et al also reported that memantine has faster unblocking kinetics than PCP and ketamine, similar to duloxetine, which is also a low-affinity antagonist of NMDA receptors, on recombinant human NMDA receptors [ 52 ] (it is described in more detail in the later Section 4.2 Mode of Fast Off-Rate and Section 4.3 Voltage Dependency).…”
Section: Why Is Memantine Free Of the Severe Side Effects Of Nmda mentioning
confidence: 99%
“…Low affinity/fast off-rate [45,50,51,53] Voltage dependency/fast unblocking kinetics [50][51][52][53][54][55] Partial trapping [54][55][56] Uncompetitive antagonism/ agonist concentration dependency [53,[57][58][59][60] Preferential inhibition of extrasynaptic receptors [65][66][67][68][69][70]…”
Section: Mode Of Actions Main Referencesmentioning
confidence: 99%
“…The affinity for NMDAR was determined using [ 3 H]MK-801 radioligand binding in rat cerebrum homogenate as previously described [ 15 , 16 ]. A comparison of the inhibition of glutamate/glycine currents in oocytes expressing human NR1/NR2A or NR1/NR2B NMDAR was made using patch clamp as previously described [ 17 ]. Patch clamp electrophysiology studies to investigate concentration and voltage dependence of NMDAR currents were conducted in HEK293 NMDA NR1/2A TET-inducible cells as previously described [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%